Transforming Escalation to Negotiation: Rethinking Confidence-Building Measures (CBMs) in the Ongoing Russia-Ukraine War (British Journal of Multidisciplinary and Advanced Studies, 2024)
There have been several pieces of literature on the current war between Russia and Ukraine but little emphasis has been placed on transforming the growing escalation into negotiation. In this study, I discuss the causalities that surround the current war between the Russian Federation and Ukraine from different prisms. Various justifications and other indices which provide the likelihood of escalation to a nuclear conflict were touched. Also, I assessed, if at all, there was politics behind the supplies of ‘defensive weapons’ and other military aid to the warring parties. I propose an urgent arms control treaty not only between the United States and Russia but should also include China as the emerged third force, and other minor nuclear powers. Although, the Confidence Building Measures (CBMs) are mostly prominent before a complex conflict is transformed into conventional war, thus, this study suggests the roles the CBMs can still play in the current war. As such, the study relies on relevant written sources which make the study qualitative in nature.